Multilayer diaphragm based on active material coating and organic flame-retardant material coating as well as preparation method and application of multilayer diaphragm

By coating the positive electrode active material and flame-retardant natural organic materials on the PVDF-HFP diaphragm of lithium-ion batteries, breaking the traditional separator structure, solving the safety hazards of the lithium-ion battery separator in terms of puncture and heat shrinkability, and achieving improvements Effects of battery capacity and safety performance.

CN119447706AActive Publication Date: 2025-02-14YANGTZE DELTA REGION INST OF UNIV OF ELECTRONICS SCI & TECH OF CHINE (HUZHOU)
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411649046.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-14
Estimated Expiration
2044-11-19

Smart Images

  • Figure CN119447706A_ABST
    Figure CN119447706A_ABST
Patent Text Reader

Abstract

The invention discloses a multilayer diaphragm based on an active material coating and an organic flame-retardant material coating as well as a preparation method and application of the multilayer diaphragm, and the preparation method of the multilayer diaphragm comprises the following steps: A, preparing moringa oleifera flame-retardant powder; and B, preparing the multi-layer diaphragm. The multi-layer diaphragm is a three-layer diaphragm, the slurry of the first layer is prepared from moringa oleifera powder and a PVDF-HFP copolymer, the second layer is prepared from the PVDF-HFP copolymer, and the third layer contains an active material. By using the multi-layer diaphragm, the thermal stability can be improved, and the risks of short circuit and thermal runaway are reduced, so that the safety of the battery is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of energy storage materials and focuses on the design of diaphragms for lithium-ion batteries (LIBs). Its purpose is to improve the capacity and safety performance of lithium-ion batteries by designing multi-layer diaphragms and coating them with organic materials and positive electrode active materials. Technical Background

[0002] The separator is a key component of lithium-ion batteries (LIBs). It can quickly transport lithium ions while isolating the positive and negative electrode materials to prevent electrical short circuits, and plays a vital role in the safety, life and energy density of lithium batteries. Academia and industry have conducted extensive research on the design and development of separators to ensure the safety of batteries. However, the puncture and significant thermal shrinkage of the separator pose a threat to battery safety. Two important breakthroughs in separator technology are Celgard's multilayer polyolefin separator with thermal shutdown mechanism, and the heat-resistant ceramic-coated polyolefin separator developed by companies such as Hitachi Maxell and Degussa. However, coating inert ceramics on polyolefin separators will have a "dead weight" effect on battery capacity, and the ultra-thin inert ceramic layer may collapse after the polyolefin film is heated and melted, resulting in battery short circuit and thermal runaway.

[0003] The development of separators with high mechanical strength, high temperature resistance and flame retardancy is crucial for battery performance and safety. Many high-strength polymer materials, such as polyimide (PI), polybenzimidazole (PBI), polyetherimide (PEI), polyetheretherketone (PEEK) and poly(m-phenylene isophthalamide) (PMIA), have been used in battery separators, but these materials are difficult to process into thin films (sheets) and are costly, limiting their large-scale application. Flame-retardant polymers and coating materials, such as PI and PBI, have also been used to prepare separators, but processing technology and cost remain challenges. Traditional single polymer separators are difficult to meet the requirements of battery performance and safety. Surface modification, mixing of inorganic and organic materials, and designing multilayer structures are effective methods to improve commercial polyolefin separators, PVDF-based separators and other polymer separators. In addition, replacing liquid electrolytes and separators with solid electrolytes can eliminate safety hazards such as toxicity, leakage and flammability, but the low ionic conductivity of solid-state batteries at room temperature and poor stability of the electrode / electrolyte interface are its main obstacles. Therefore, improving liquid battery separators is still of great significance. Summary of the invention

[0004] The present invention aims to solve the shortcomings of traditional inert ceramic diaphragms by introducing a multilayer structure design, coating positive electrode active materials and flame retardant organic materials on polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) diaphragms. This method does not require the use of expensive and complex polymer materials, and can coat the diaphragm with positive electrode active materials for lithium-ion batteries, such as lithium iron phosphate (LFP), ternary NMC and lithium cobalt oxide (LiCoO2); as well as flame retardant natural (organic) materials such as moringa leaf powder. The active material coating not only has excellent heat resistance, but also creates an electrical conductance path and undergoes an electrochemical reaction with the positive electrode, thereby providing additional capacity.

[0005] The key scientific issues of the present invention are:

[0006] 1. Relationship between composition, structure and performance of multilayer separators for lithium-ion batteries:

[0007] Separators are one of the most critical components in lithium-ion batteries. Although they do not directly participate in the electrochemical reactions within the battery, separators prevent contact between electrodes, avoid internal short circuits, store liquid electrolytes, and enable efficient ion transport during charge and discharge. The traditional battery structure is "positive electrode||separator||negative electrode". In this concept, by adding two additional components to the battery, namely "positive electrode||positive electrode active material layer / separator substrate layer / Moringa flame retardant layer||negative electrode", the number of components and interfaces increases significantly. By controlling the composition and structure of the separator and studying the battery performance, the relationship between the composition, structure and performance (capacity, rate, safety) of the multilayer separator can be established. This will help to rationally design lithium battery separators and provide guidance for the development of high-performance lithium battery separators.

[0008] 2. Charging and ion transport mechanisms of multilayer separators for lithium-ion batteries:

[0009] The complex porous structure of the multilayer diaphragm design has established a new system for studying ion diffusion and lithium deposition behavior in porous media. There is a complex charge and ion transport mechanism between the active ceramic layer of the diaphragm and the electrode interface. The study of the quality and charge transport characteristics of this interface, as well as the flame retardant ability of organic materials, through experimental and theoretical methods can enrich the electrochemical research system and provide a theoretical basis for the development of high-capacity and high-safety chemical power sources with similar structures.

[0010] The goal of this invention is to address the safety and performance challenges of lithium-ion batteries (LIBs) through an innovative multilayer separator design. Specific goals include:

[0011] 1. Improve the capacity and safety of lithium-ion batteries:

[0012] Develop multilayer separators coated with organic materials and cathode active materials to improve the capacity and safety of lithium-ion batteries.

[0013] By allowing the separator to participate in the electrochemical reaction process, the battery capacity is increased.

[0014] 2. Flame retardant and explosion-proof design:

[0015] The safety of lithium-ion batteries is improved by introducing a flame-retardant layer made of natural Moringa material to prevent fire and explosion risks.

[0016] Improving the battery's resistance to thermal shrinkage and high-temperature conditions is key to preventing internal short circuits and thermal runaway.

[0017] 3. Mass and charge transport mechanisms:

[0018] Study the quality and charge transport mechanisms at the electrode / active ceramic-coated separator interface to enhance the understanding and control of lithium-ion battery performance.

[0019] Study the flame retardant and anti-dendrite mechanisms of Moringa coatings to guide the improvement of battery performance and safety.

[0020] 4. Cost-effective and sustainable solution:

[0021] By avoiding the use of expensive polymer materials, it provides a cost-effective separator alternative, utilizing natural organic materials such as Moringa, which also has environmental advantages.

[0022] 5. Improve thermal stability and mechanical strength:

[0023] The separator is designed with high thermal stability and mechanical strength to ensure that the battery remains safe and functional under extreme conditions.

[0024] 6. Structural innovation of lithium-ion batteries:

[0025] By introducing a multi-layer separator with an additional active material layer and a flame-retardant organic material layer, the traditional "positive electrode||separator||negative electrode" battery structure is broken. This design aims to enhance thermal stability and mechanical strength, thereby improving overall battery performance.

[0026] In order to achieve the technical purpose of the present invention, the present invention adopts the following technical solution:

[0027] A method for preparing a multilayer diaphragm based on an active material coating and an organic flame retardant material coating comprises the following steps:

[0028] A. Preparation of Moringa flame retardant powder;

[0029] B. Preparation of multilayer membranes.

[0030] Furthermore, the preparation method of Moringa flame retardant powder in step A comprises the following steps:

[0031] The Moringa leaves were dried in an oven at 80°C for 24 hours to obtain dried Moringa leaves, which were then manually ground to obtain leaf powder. The leaf powder was then ball-milled at 500 rpm for 4-8 hours to prepare fine leaf powder particles, and the ball-milled suspension was centrifuged at 5000 rpm for three times for 15 minutes each, and then dried at 80°C for 12 hours to obtain dried Moringa powder.

[0032] Furthermore, the multi-layer membrane in step B is a three-layer membrane.

[0033] Further, the slurry of the first layer will be prepared from Moringa powder and PVDF-HFP copolymer.

[0034] Furthermore, the preparation method of the first layer includes the following steps: dissolving PVDF-HFP in acetone at room temperature for 5 to 10 minutes, and then stirring at 50°C until it becomes transparent. After preparing the PVDF-HFP matrix, adding moringa powder and acetone and stirring for 2 hours, and then applying the prepared solution with a scraper to a thickness of 10 microns on the substrate, and drying at room temperature to obtain a PVDF-HFP / moringa particle composite coating based on a paper substrate.

[0035] Furthermore, the second layer is made of PVDF-HFP copolymer.

[0036] Furthermore, the preparation method of the second layer includes the following steps: dissolving PVDF-HFP in acetone at room temperature for 5 to 10 minutes, and then stirring at 50°C until it becomes transparent. After preparing the PVDF-HFP matrix, stirring for 2 hours, and then applying the prepared solution to a thickness of 10 microns on the substrate with a scraper, and drying at room temperature to obtain a second coating.

[0037] Further, the third layer contains an active material.

[0038] Furthermore, the choice of the active material will depend on the type of cathode used, such as LFP, NMC or LiCoO2.

[0039] Furthermore, the preparation method of the third layer includes the following steps: dissolving PVDF in NMP, then adding active materials and carbon, stirring at room temperature for 6 hours, and coating with a thickness of 10 microns on the substrate already coated with the first layer and the second layer, and then drying at 60°C for 12 hours.

[0040] The present invention can improve the capacity and safety performance of lithium-ion batteries by developing a multilayer diaphragm design with a complex porous structure, coating active materials on the positive electrode side, and using Moringa (organic material) powder with flame retardant ability. The proposed lithium-ion battery diaphragm will have the following characteristics:

[0041] 1. The multilayer separator design with complex porous structure will improve the wettability and retention of electrolyte, thereby improving ionic conductivity; in addition, this structure helps prevent the dendrite structure from penetrating from the negative electrode to the positive electrode.

[0042] 2. The active layer coated on the cathode side will ensure the compatibility of the separator and cathode interface and improve the chemical stability.

[0043] 3. The coating of active layer will enhance the electrochemical performance because the active layer of the separator participates in the charge and discharge process.

[0044] 4. The Moringa layer coated on the negative electrode side will inhibit the growth of lithium dendrites and have good flame retardancy, avoiding serious problems caused by internal short circuits.

[0045] 5. The proposed diaphragm will have high thermal and mechanical stability and can resist the shrinkage of the diaphragm at high temperature.

[0046] 6. The proposed separator thickness is less than 25 μm or thinner, which will not affect the overall energy density of lithium-ion batteries.

[0047] The innovative features of the present invention are as follows:

[0048] 1. Technological innovation: The traditional battery structure is "positive electrode||diaphragm||negative electrode". In this work, the sandwich structure of the traditional battery is broken by adding two additional components to the battery, namely "positive electrode||positive electrode active material layer / diaphragm substrate layer / moringa layer||negative electrode". The multilayer design and the thermodynamic mechanical stability of the positive electrode material can improve the thermal stability and mechanical strength of the diaphragm, reduce the thermal shrinkage of the diaphragm, and avoid internal short circuits. In addition, the flame retardant layer of the diaphragm uses moringa, which has a "natural flame retardant" effect due to its antioxidant properties, thereby reducing the possibility of fire / explosion in any severe situation. The proposed multilayer diaphragm has strong thermomechanical stability and flame retardant properties, which can significantly improve the safety of lithium-ion batteries. On the other hand, the positive electrode material coating of the diaphragm maintains physical contact with the electrode, can participate in the electrochemical reaction of the battery, increase the capacity, and achieve the purpose of "capacity enhancement".

[0049] 2. Theoretical innovation: The diaphragm adopts a complex porous structure and multi-layer design, the positive electrode side is coated with active materials, and the negative electrode side is coated with flame retardant materials, establishing a new system for studying ion diffusion and lithium deposition behavior in porous media. The traditional design of lithium-ion batteries provides an inert / active interface between the diaphragm and the positive electrode, while the proposed diaphragm design battery provides an active / active interface (positive electrode / diaphragm active layer), that is, positive electrode||positive electrode active material layer / diaphragm substrate layer / Moringa flame retardant layer. By experimentally and theoretically studying the quality and charge transfer characteristics of this interface and the flame retardant ability of the Moringa layer, it is possible to enrich the electrochemical research system and provide a theoretical basis for the development of high-capacity and high-safety chemical power sources with similar structures.

[0050] Compared with the prior art, the present invention has the following technical advantages:

[0051] 1. Improve battery safety: Lithium-ion batteries (LIBs) are known for safety issues, such as overheating and fire risks. The use of the multilayer separator of the present invention can improve thermal stability and reduce the risk of short circuit and thermal runaway, thereby significantly improving battery safety.

[0052] 2. Improve capacity and life: This invention aims to explore strategies to enhance the capacity and life of lithium-ion batteries. The separator will participate in the electrochemical reaction, increase the battery capacity, and remain stable under extreme conditions, thereby improving the stability of long-term use.

[0053] 3. Flame retardant properties: Organic material coatings have excellent thermal stability and flame retardant properties. This is a significant improvement for applications that require high safety standards (especially electric vehicles or other high-power energy storage systems).

[0054] 4. Enhanced performance under extreme conditions: In many applications, high temperature performance is critical. Separators coated with active ceramics and organic materials can maintain battery performance under harsh conditions, potentially making them more suitable for extreme environments.

[0055] 5. Wider applications in energy storage systems: This research could open up new possibilities for the use of lithium-ion batteries in large-scale energy storage systems, where capacity and safety are equally important.

[0056] 6. Environmental and economic benefits: Improving the performance and safety of lithium-ion batteries can lead to more sustainable energy storage solutions, reducing the need for frequent replacement and thus reducing waste. This also has potential long-term cost savings benefits.

[0057] These advantages indicate that the present invention has great potential for technological innovation in the field of energy storage and lithium-ion battery safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 Schematic diagram of failure mechanism of high temperature stability of membrane;

[0059] Figure 2 It is the overall technical scheme diagram of the present invention;

[0060] Figure 3 Schematic diagram of the preparation of Moringa flame retardant powder;

[0061] Figure 4 Schematic diagram of the preparation of the first layer of the multilayer diaphragm;

[0062] Figure 5 Schematic diagram of the preparation of the second layer of the multilayer diaphragm;

[0063] Figure 6 Schematic diagram of the preparation of the third layer of the multilayer diaphragm;

[0064] Figure 7 Schematic diagram of separator placement in lithium-ion batteries;

[0065] Figure 8 Schematic diagram of the battery preparation for in situ Raman analysis. DETAILED DESCRIPTION

[0066] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. On the contrary, the present invention encompasses any substitutions, modifications, equivalent methods and schemes made on the essence and scope of the present invention as defined by the claims. Further, in order to enable the public to have a better understanding of the present invention, some specific details are described in detail in the detailed description of the present invention below. For those skilled in the art, the present invention can be fully understood without the description of these details.

[0067] like Figure 1 , 2As shown, in the embodiment of the present invention, a simple and cost-effective blade coating method will be used to prepare a multilayer lithium-ion battery separator. The proposed separator consists of three layers: (a) a positive electrode active material layer, (b) a base separator, and (c) a moringa particle layer. The active material layer coated on the separator from the positive electrode side will participate in the electrochemical reaction of the lithium-ion battery and contribute to the battery capacity (capacity enhancement). In addition, the complex multilayer design of the separator has a significant effect on thermal stability, mechanical strength and ionic conductivity. These properties will be optimized through the relationship between material composition and structure. Moringa is a natural flame retardant due to its antioxidant properties. After determining the material composition and structure of the proposed separator, a lithium-ion battery will be assembled, and the capacity, rate performance and cycle performance of the lithium battery based on the separator will be studied and observed. In addition, the thermodynamic and mechanical properties of the battery under thermal runaway conditions and its explosion characteristics will also be studied. Further in situ experimental techniques, such as in situ Raman spectroscopy and finite element analysis based on mass transfer and charge transfer models, will be used to study the capacity enhancement mechanism and flame retardant mechanism of the separator.

[0068] 1. Multilayer membrane construction based on active material coating and organic flame retardant material (Moringa material) coating:

[0069] A. Preparation of Moringa Flame Retardant Powder: In the proposed multi-layer membrane concept, Moringa leaves will serve as a "natural flame retardant" material in the membrane to help prevent fire, explosion or thermal runaway. Figure 3 As shown, first, the Moringa leaves were dried in an oven at 80°C for 24 hours to obtain dried Moringa leaves, which were then manually ground to obtain leaf powder. Then, the leaf powder was ball-milled at 500 rpm for 4-8 hours to prepare fine leaf powder particles, and then the ball-milled suspension was centrifuged at 5000 rpm for 15 minutes each three times, and then dried at 80°C for 12 hours to obtain dried Moringa powder.

[0070] B. Preparation of multilayer membrane: The preparation of multilayer membrane (three layers) is divided into three steps, such as Figure 4-6 The detailed preparation process is as follows:

[0071] First layer: The slurry of this layer will be prepared from Moringa powder and PVDF-HFP copolymer. First, PVDF-HFP is dissolved in acetone at room temperature for 5 to 10 minutes, and then stirred at 50°C until it is transparent. After the PVDF-HFP matrix is ​​prepared, Moringa powder, acetone are added and stirred for 2 hours. Then, the prepared solution is coated on the substrate with a thickness of 10 microns using a doctor blade and dried at room temperature to obtain a PVDF-HFP / Moringa particle composite coating based on a paper substrate.

[0072] Second layer: This layer will be made of PVDF-HFP copolymer. The preparation method of PVDF-HFP solution is the same as the first layer, except that Moringa powder and acetone are not added. The PVDF-HFP solution is coated on the substrate with the same thickness as the first layer, 10 microns.

[0073] Third layer: This layer will contain the active material (the choice of active material will depend on the type of cathode used, such as LFP, NMC or LiCoO2). The slurry will be prepared in NMP by the active material, carbon and PVDF binder in a certain proportion. First, PVDF is dissolved in NMP, then the active material and carbon are added, stirred at room temperature for 6 hours, and coated with a thickness of 10 microns on the substrate already coated with the first and second layers, and then dried at 60°C for 12 hours.

[0074] 2. Characterization methods and analysis:

[0075] Different characterization techniques are employed to observe the properties and behavior of the multilayer separators. The following provides details on the characterizations and related analyses that will be performed during the work:

[0076]

[0077] 3. Study on electrochemical performance of lithium-ion batteries based on multilayer separators:

[0078] like Figure 7 As shown, the lithium-ion battery with multilayer separator will be assembled in an argon-filled glove box for electrochemical performance testing. During the battery assembly process, ensure that the active material coated on the separator corresponds to the type of positive electrode material (for example, when LFP material is coated on the separator, the positive electrode must be LFP). The Moringa flame retardant layer of the separator should face the negative electrode side. The following are the details of the electrochemical characterization and related analysis:

[0079]

[0080] 4. Research on safety performance of lithium-ion batteries based on multilayer separators:

[0081] For the safety analysis of lithium-ion batteries, flexible lithium-ion batteries will be assembled using multi-layer active flame-retardant separators and traditional separators. Two different tests will be conducted to examine the safety of the battery during charging and discharging by changing the temperature.

[0082]

[0083]

[0084] 5. In-situ Raman analysis of the interface between the diaphragm and the electrode:

[0085] For in situ Raman analysis of the separator / electrode interface, lithium-ion button cells were assembled as specified. Figure 8 As shown, this analysis will reveal in detail the impact of separator coating materials or separator design on the performance of lithium-ion batteries.

[0086] A. Focusing the laser beam from the positive electrode side: In order to analyze the interface between the battery active layer and the positive electrode, the laser beam will be continuously focused on the separator coated with the active material layer during the charge and discharge process of the lithium-ion battery. The in-situ Raman spectra changes of lithium-ion batteries based on the proposed separator and traditional separators will be observed and the final conclusion will be drawn.

[0087] B. Focusing the laser beam from the negative electrode side: In order to analyze the interface between the Moringa coating and the negative electrode of the battery, the laser beam will be continuously focused on the Moringa coating of the separator during the charge and discharge process of the lithium-ion battery. The in-situ Raman spectra changes of lithium-ion batteries based on the proposed separator and traditional separators will be observed and the final conclusion will be drawn.

[0088] Material Details:

[0089]

[0090]

Claims

1. A method for preparing a multilayer diaphragm based on an active material coating and an organic flame retardant material coating, characterized in that: The following steps are involved: A. Preparation of Moringa flame retardant powder; B. Preparation of multilayer membranes.

2. The method for preparing a multilayer diaphragm based on an active material coating and an organic flame retardant material coating according to claim 1, characterized in that: The preparation method of Moringa flame retardant powder in step A comprises the following steps: The Moringa leaves were dried in an oven at 80°C for 24 hours to obtain dried Moringa leaves, which were then manually ground to obtain leaf powder. The leaf powder was then ball-milled at 500 rpm for 4-8 hours to prepare fine leaf powder particles, and the ball-milled suspension was centrifuged at 5000 rpm for three times for 15 minutes each, and then dried at 80°C for 12 hours to obtain dried Moringa powder.

3. The method for preparing a multilayer diaphragm based on an active material coating and an organic flame retardant material coating according to claim 1, characterized in that: The multilayer membrane in step B is a three-layer membrane, which includes a first layer, a second layer, and a third layer. The slurry of the first layer is prepared from Moringa powder and PVDF-HFP copolymer.

4. The method for preparing a multilayer diaphragm based on an active material coating and an organic flame retardant material coating according to claim 3, characterized in that: The preparation method of the first layer includes the following steps: dissolving PVDF-HFP in acetone at room temperature for 5 to 10 minutes, and then stirring at 50°C until it becomes transparent. After preparing the PVDF-HFP matrix, adding moringa powder and acetone and stirring for 2 hours, and then applying the prepared solution on the substrate with a scraper to a thickness of 10 microns, and drying at room temperature to obtain a PVDF-HFP / moringa particle composite coating based on a paper substrate.

5. The method for preparing a multilayer diaphragm based on an active material coating and an organic flame retardant material coating according to claim 3, characterized in that: The second layer is made of PVDF-HFP copolymer.

6. The method for preparing a multilayer diaphragm based on an active material coating and an organic flame retardant material coating according to claim 5, characterized in that: The preparation method of the second layer includes the following steps: dissolving PVDF-HFP in acetone at room temperature for 5 to 10 minutes, and then stirring at 50°C until it becomes transparent. After preparing the PVDF-HFP matrix, stirring for 2 hours, and then coating the prepared solution with a scraper to a thickness of 10 microns on the substrate, and drying at room temperature to obtain a second coating.

7. The method for preparing a multilayer diaphragm based on an active material coating and an organic flame retardant material coating according to claim 3, characterized in that: The third layer contains the active material, the choice of which will depend on the type of cathode used, such as LFP, NMC or LiCoO2.

8. The method for preparing a multilayer diaphragm based on an active material coating and an organic flame retardant material coating according to claim 7, characterized in that: The preparation method of the third layer includes the following steps: dissolving PVDF in NMP, then adding active materials and carbon, stirring at room temperature for 6 hours, and coating with a thickness of 10 microns on the substrate already coated with the first layer and the second layer, and then drying at 60°C for 12 hours.

9. A multilayer separator based on an active material coating and an organic flame retardant material coating prepared according to the method of any one of claims 1 to 8.

10. Use of the multilayer separator based on active material coating and organic flame retardant material coating according to claim 9 in the preparation of lithium ion batteries.

Citation Information

Patent Citations

  • Porous moringa oleifera particles, preparation method of porous moringa oleifera particles as well as cigarette filter stick containing porous particles

    CN104687246A

  • Inflame-retardant mine cabtyre cable sheath material

    CN105199243A

  • Anti-UV and anti-aging electric wire cable material and preparation method thereof

    CN105670160A

  • High-temperature wear-resistant composite material and preparation method thereof

    CN109021490A

  • Lithium ion battery composite diaphragm and preparation method thereof

    CN113328207A